Organosolv Pretreatment Process and Hydrolysis Acid Conversion Oil Palm Frond (OPF) as Bioetanol Raw Material - ., Saisa; Husin, Husni; ., Mahidin (International Journal of Engineering and Technology, 2019)
This research uses a palm frond as a source holoselulosa be converted into raw materials for bioethanol (total sugars). This research aims to study the pretreatment process organosolv with ethanol and acid hydrolysis of the palm frond conversion into sugar. The process of making sugar from palm frond begins with a process of delignification and be followed by a process of hydrolysis. Delignification process takes place in conditions with varying concentrations of ethanol 35%, 55%, 75%, and 90% v/v at 1000C and 1200C and reaction time 60 and 90 minutes. Furthermore, for hydrolysis process using sulfuric acid with variation of concentration 1%, temperature 60, 70, 80, 90 and 1000C and reaction time 15, 30, 45, 60 and 75 minutes. The results showed that in the delignification condition with 75% C 2H5OH concentration, 1200C for 60 minutes and 1% catalyst (H2SO4) and under 1% H2SO4 hydrolysis condition, 30 min and 900C, the highest total sugar yield 93.65 mg/L.Â Â